Tobramycin inhalation powder (TOBI Podhaler®) for the treatment of lung infection in patients with cystic fibrosis. Issue 1 (2nd January 2016) - Vazquez-Espinosa, E.; Marcos, C.; Alonso, T.; Giron, R.M.; Gomez-Punter, R.M.; Garcia-Castillo, E.; Zamora, E.; Cisneros, C.; Garcia, J.; Valenzuela, C.; Ancochea, J.
Abstract : Cystic fibrosis (CF) is an autosomal recessive inherited disease secondary to a defect in the CF transmembrane conductance regulator gene ( CFTR ). Mortality in CF is associated with impairment of lung function in which bacterial infection plays a fundamental role. The microorganism Pseudomonas aeruginosa ( P. aeruginosa) is a marker of poor prognosis. Tobramycin was the first parenteral antibiotic to be used as inhaled medication in CF. Owing to its beneficial effects; it was subsequently used in designed inhaled formulations. The first formulation was the inhalation solution, which improved lung function, lowered hospitalization rates, and reduced the courses of intravenous antibiotic. However, the high associated costs and time necessary to administer the medication negatively affected quality of life. The recent development of tobramycin inhalation powder has optimized treatment. The dry powder inhaler is a simple device that reduces administration time and improves adherence. As there is no risk of bacterial contamination, disinfection is unnecessary.